Pengaruh Citra Merek, Persepsi Harga dan Kualitas Produk Terhadap Keputusan Pembelian Makanan Kucing Merek Cat Choice di Toko Phiko Cat Shop Balikpapan - Winny Gusmiranda; Dewi Sartika (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study seeks to examine the influence of Brand Image, Price Perception and Product Quality on Purchasing Decisions, both individually and simultaneously. The research adopts a quantitative approach, utilizing primary and secondary data sources. Primary data were collected through respondents, observations, and documentation, with a sample size of 96 respondents. Data analysis methods include Validity and Reliability Testing, Multiple Linear Regression Analysis and Hypothesis Testing, conducted using SPSS version 20. The findings indicate that: (1) Brand Image, Price Perception, and Product Quality collectively have a significant impact on the Purchase Decision of Cat Choice Brand Cat Food at Phiko Cat Shop Balikpapan; (2) Brand Image individually has a significant effect on the Purchase Decision of Cat Choice Brand Cat Food at Phiko Cat Shop Balikpapan; (3) Price Perception individually has a significant effect on the Purchase Decision of Cat Choice Brand Cat Food at Phiko Cat Shop Balikpapan; and (4) Product Quality individually has a significant effect on the Purchase Decision of Cat Choice Brand Cat Food at Phiko Cat Shop Balikpapan.